The state of our cities evidence from Karnataka - Paul, Samuel (New Delhi ; Oxford : Oxford University Press, 2012)
The rapid pace of urbanization in India is examined in this case study covering 15 major cities in the state of Karnataka. It develops indicators & benchmarks for six thematic areas that capture the synamics & potential or urban areas: history & governance; demographics; economic dimensions; infrastructure & public services; resources; and quality of life.
Description based on online resource; title from PDF title page (viewed on Aug. 15, 2012).
Keywords: Cities and towns -- India -- Karnataka -- Growth; Urbanization -- India -- Karnataka; City and town life -- India -- Karnataka